Young children, gender and the heterosexual matrix. Issue 2 (4th March 2017) - Paechter, Carrie
ABSTRACT: In this paper I consider the adult focus of current mainstream gender theory. I relate this to how the concept of the heterosexual matrix originates in a social contract which excludes children from civil society. I argue that this exclusion is problematic both for theoretical reasons and from the perspective of children themselves. I start by discussing the nature of the heterosexual matrix and its foundations. I consider the implications for participation which arise from being named as a child, how that affects children's attempts to claim participation in civil society, and how this is related to children's naming of themselves as gendered. I then briefly consider the possibility that, because of their exclusion, children might also be considered to be exempt from the heterosexual matrix. However, I argue, there is considerable evidence that children are actively sexual beings who also work hard to claim inclusion in local practices of heterosexuality. I end by suggesting that there are three key reasons for this: that the discourses of normative sexuality provide children with a language to express sexual feelings; that self-insertion in the heterosexual matrix is a way for children to claim rights to participation; and that taking up heterosexual formations is a means whereby children can experience the power of naming themselves as part of the social world.